2013
DOI: 10.1159/000350145
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria as a Risk Factor for Decline in Residual Renal Function in Non-Diabetic Peritoneal Dialysis Patients

Abstract: Background: Preservation of residual renal function (RRF) is a major issue for patients on peritoneal dialysis (PD). Whether proteinuria is associated with a decline in RRF in patients on PD remains unclear. Patients and Methods: We reviewed the medical records at the Yeungnam University Hospital in Korea and identified patients who started PD between June 1995 and August 2011. A total of 147 non-diabetic patients were enrolled in the study. The patients were divided into 3 groups with respect to the tertile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Moreover, proteinuria was present in all children who became anuric in the studied period, with 90.9% of them having nephrotic range proteinuria. These results, similarly to findings in adult patients (3,16,17), indicate a strong adverse effect of large proteinuria on renal function also after initiation of RRT.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, proteinuria was present in all children who became anuric in the studied period, with 90.9% of them having nephrotic range proteinuria. These results, similarly to findings in adult patients (3,16,17), indicate a strong adverse effect of large proteinuria on renal function also after initiation of RRT.…”
Section: Discussionsupporting
confidence: 86%
“…Since data in table 3 suggested that the patients treated with fewer initial HD frequency had less incidence of RKF loss than patients treated with regular thrice-weekly HD, a Receiver Operating Characteristic (ROC) analysis was performed to decide the cut-off value of a 50% decline rate of GFR in a year for predicting whether the patient has lost RKF or not, as previously reported [35,36]. We found the best cut-off value was 0.044 (4.4%) with a specificity of 75% and a sensitivity of 64% (AUC = 0.65, p < 0.05) (see online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, patients in the early peritonitis group were older and exhibited a lower ALB level, either of which can negatively impact patient outcomes. Besides, lower ALB level and proteinuria may cause decline in residual renal function, which can worsen the prognosis of PD patients [20].…”
Section: Discussionmentioning
confidence: 99%